Addicted to incarceration : corrections policy and the politics of misinformation in the United States - Pratt, Travis C. (Los Angeles, CA : SAGE Publications, Inc., 2019)
In Addicted to Incarceration, author Travis C. Pratt uses an evidence-based approach to explore the consequences of what he terms America's "addiction to incarceration." Highlighting the scope of the issue, the nature of the political discussions surrounding criminal justice policy in general and corrections policy in particular, and the complex social cost of incarceration, this book takes an incisive look at the approach to corrections in the United States. The Second Edition demonstrates that the United States' addiction to incarceration has been fueled by American citizens' opinions about crime and punishment, the use of incarceration as a means of social control, and perhaps most important, by policies legitimized by faulty information. Analyzing crime policies as they relate to crime rates and society's ability to both lower the crime rate and address the role of incarceration in preventing future crime, this book shows students how ineffective the rush to incarcerate has been in the past and offers recommendations and insights to navigate this significant problem going forward.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Imprisonment -- Government policy -- United States; Corrections -- Government policy -- United States